Iklim Komunikasi Organisasi Unit Kegiatan Mahasiswa (UKM) Keluarga Mahasiswa Katolik (KMK) Universitas Ciputra Surabaya Periode 2023/2024 - Husodo, Chrestella Angelica (CV. ITTC INDONESIA, 2025)
Communication is a fundamental aspect of human life, serving to exchange thoughts, opinions, and ideas. Through communication, social interactions are formed, which in turn give rise to social systems or organizations. Within an organization, communication dynamics present a unique challenge, as they involve individuals with diverse backgrounds, ways of thinking, and personalities. One of the most common challenges encountered is miscommunication, which can lead to disharmony in interpersonal relationships. Such disharmony has the potential to hinder team effectiveness and the achievement of organizational goals. This phenomenon is also observed in the context of the Student Activity Unit (UKM) Catholic Student Family (KMK). The patterns of relationships and interactions that develop within this organization ultimately create a condition known as the communication climate. Therefore, this study aims to explore the organizational communication climate within UKM KMK during the 2023/2024 period. The research employs a quasi-qualitative method, with data collection techniques including interviews and document analysis. The findings reveal that the organizational communication climate of UKM KMK during the 2023/2024 period is categorized as positive. This is attributed to the organization's ability to implement six key factors that influence the communication climate. These factors include the development of trust through bonding activities, the opportunity for all members to voice their opinions, openness to providing evaluations for collective improvement, the practice of two-way communication, and a shared commitment to high-performance goals.